The Language, Tone and Prosody of Emotions: Neural Substrates and Dynamics of Spoken-Word Emotion Perception - Liebenthal, Einat; Silbersweig, David A.; Stern, Emily (Frontiers in Neuroscience, 2016)
Rapid assessment of emotions is important for detecting and prioritizing salient input. Emotions are conveyed in spoken words via verbal and non-verbal channels that are mutually informative and unveil in parallel over time, but the neural dynamics and interactions of these processes are not well understood. In this paper, we review the literature on emotion perception in faces, written words, and voices, as a basis for understanding the functional organization of emotion perception in spoken words. The characteristics of visual and auditory routes to the amygdala – a subcortical center for emotion perception – are compared across these stimulus classes in terms of neural dynamics, hemispheric lateralization, and functionality. Converging results from neuroimaging, electrophysiological, and lesion studies suggest the existence of an afferent route to the amygdala and primary visual cortex for fast and subliminal processing of coarse emotional face cues. We suggest that a fast route to the amygdala may also function for brief non-verbal vocalizations (e.g., laugh, cry), in which emotional category is conveyed effectively by voice tone and intensity. However, emotional prosody which evolves on longer time scales and is conveyed by fine-grained spectral cues appears to be processed via a slower, indirect cortical route. For verbal emotional content, the bulk of current evidence, indicating predominant left lateralization of the amygdala response and timing of emotional effects attributable to speeded lexical access, appears more consistent with an indirect cortical route to the amygdala. Top-down linguistic modulation may play an important role for prioritized perception of emotions in words. Understanding the neural dynamics and interactions of emotion and language perception is important for selecting potent stimuli and devising effective training and/or treatment approaches for the alleviation of emotional dysfunction across a range of neuropsychiatric states.